Pekarangan Ngajeng Wong Kalang, keselarasan dengan alam: Pendekatan etnografi di Desa Kalang, Desa Lumansari, Kecamatan Gemuh, Kabupaten Kendal-Jawa Tengah - Setio, Stefanus Prabani; Putra, Heristama Anugerah (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
Pekarangan ngajeng (Ngajeng yard) is an open area at the front of the residence. Ngajeng yards are formed based on the division of residential land. The formation of the Ngajeng yard is based on tradition. The Ngajeng yard's use is determined by social, religious, traditional, and agricultural factors. The ngajeng yard is still preserved by the Kalang village's Javanese sub-ethnic group, the Kalang. The advantage of the ngajeng yard space as a path for the sun's movement is provided by the Limasap house, where the Kalang people reside, being oriented towards the North and South. Specifically, the objective of the ngajeng yard following the direction of the sun's movement will be covered in this research. The methods used are 1) ethnography, describing traditions related to the Ngajeng yard as well as religious aspects and beliefs of the Kalang people; 2) Analysis of the sun's movement in the East to West trajectory. The orientation of the traditional Limasap omah (house) building influences the existence of the ngajeng yard; 3) The next stage is looking for a belief system through ontology, explanation, prediction, axiology, practice, and epistemology approaches. At this stage, a belief system about the Ngajeng yard is obtained. Thus, it can be concluded that the Ngajeng yard is an open space that has various functions for the Kalang people. These functions are 1) Social function, as a communication, mitigation, and security space; 2) The function of tradition, as a space for the obong tradition to lead ancestors to nirvana; 3) Agricultural function, related to tandur (planting) traditions and harvest traditions. The belief system that is formed is a legacy of tradition related to the implementation of the wong (people) Kalang tradition.